1977
DOI: 10.1007/bf00561782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorpromazine on blood glucose and plasma insulin in man

Abstract: In three groups of normal subjects and in one group of patients with latent diabetes mellitus a study has been made of the effects of chlorpromazine (CPZ) on blood glucose and plasma insulin. CPZ 75 mg/day for 7 days did not alter the plasma insulin response after oral glucose; nor did CPZ 50 mg/day for 7 days affect the glucose assimilation rate or insulin response to glucose injection. Infusion of CPZ 50 mg in 60 min slightly increased the basal blood glucose level but had no significant effect on basal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…As in vitro (Cabrera et al 1988) and in vivo animal studies (Matsuda & Mori 1996;Reiss et al 1996) and some clinical studies (Beumont & Bergen 1982;Erle et al 1977;Foss et al 1995) have implied that hyperprolactinaemia impairs glucose tolerance and induces insulin resistance, we tested here the hypothesis that female rats rendered obese by sulpiride may display hyperinsulinaemia (and perhaps hyperglycaemia) as a compensatory mechanism to overcome insulin resistance. This way, the proposed hyperinsulinaemia (by its anabolic effect) might be an additional mechanism in neuroleptic-induced obesity in this animal model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in vitro (Cabrera et al 1988) and in vivo animal studies (Matsuda & Mori 1996;Reiss et al 1996) and some clinical studies (Beumont & Bergen 1982;Erle et al 1977;Foss et al 1995) have implied that hyperprolactinaemia impairs glucose tolerance and induces insulin resistance, we tested here the hypothesis that female rats rendered obese by sulpiride may display hyperinsulinaemia (and perhaps hyperglycaemia) as a compensatory mechanism to overcome insulin resistance. This way, the proposed hyperinsulinaemia (by its anabolic effect) might be an additional mechanism in neuroleptic-induced obesity in this animal model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causal effects of hyperprolactinaemia on insulin sensitivityhesistance have not been definitely proven, and additional research is required. Differences may also arise from using in vitro protocols such as the assessment of insulin receptor number in the adipocytes (Cabrera et al 1988) or in vivo procedures evaluating serum glucose and insulin levels (Cabrera et al 1988;Matsuda & Mori 1996;Reiss et al 1996), male (Reiss et al 1996) or female subjects (Cabrera et al 1988;Matsuda & Mori 1996), and humans (Beumont & Bergen 1982;Erle et al 1977;Foss et al 1995), mice (Matsuda & Mori 1996) or rats (Cabrera et al 1988;Reiss et al 1996). And finally, this experiment was on purpose conducted when the rats were in a very active phase of body weight gain, and this variable was not apparently considered in other experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Alguns relatos sugerem que as fenotiazinas reduzem a secreção da insulina e aumentam a liberação de catecolaminas. 19 Estes resultados, porém, ainda não foram reproduzidos. Além disso, receptores da serotonina (5-HT 1A e 5-HT 2 ) podem estar envolvidos no controle glicêmico, reduzindo a responsividade das células beta pancreáticas aos níveis sanguíneos de glicose.…”
Section: Mecanismos Geraisunclassified
“…Furthermore, Thonnard-Neumann (24) reported that the phenothiazine derivative increased the rate of patients becoming diabetic and called this phenomenon "phenothiazine diabetes". In addition, Erle et al (25) report that higher acute doses of the drug may induce hyperglycaemia and can inhibit insulin secretion both in normal individuals and in patients with latent diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%